Breast Carcinoma with Choriocarcinomatous Features: A Case Report - Sung, Hyun-Jung (Korean Breast Cancer Society, 2013)
Nongestational choriocarcinoma differentiation is extremely rare in breast neoplasms. It is characterized by tumor cells similar to chorionic trophoblastic cells, which react with human placental lactogen and human chorionic gonadotropin (hCG). A 56-year-old woman presented with a palpable right breast mass without past history of trophoblastic tumors. An F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) scan revealed one focus with low accumulation of FDG in the right breast (maximum standardized uptake value, 1.98). The patient underwent a right mastectomy and biopsy of sentinel nodes. Microscopically, the tumor was a typical invasive ductal carcinoma with multiple foci of choriocarcinoma features. Immunohistochemistry showed that the tumor cells resembling choriocarcinoma were positive for hCG antibody, but negative for HER2/neu, estrogen receptor, and progesterone receptor. A pathologic diagnosis of breast carcinoma with choriocarcinomatous features was made. To our knowledge, this is the first report of invasive carcinoma with choriocarcinomatous features and an unusual finding of low accumulation in an F-18 FDG PET/CT scan in Korea.